Cases of granulomatosis with polyangitis (Wegener's disease) diagnosed in the regional TB dispensary - V. V. Tinkova; M. V. Lekhlyayder; N. A. Galushko; O. V. Lisina; M. E. Gelich (Туберкулез и болезни лёгких)
The article describes 2 cases when granulomatosis with polyangitis (Wegener's disease) were diagnosed in the regional TB dispensary. Publications on the main clinical, radiological and morphological manifestations of granulomatosis with polyangitis were reviewed, the specific parameters required for differential diagnosis of this disease from tuberculosis were highlighted. This article demonstrates the need for the interdisciplinary approach to the differential diagnosis of tuberculosis.